Differential Responses of Stomata and Photosynthesis to Elevated Temperature in Two Co-occurring Subtropical Forest Tree Species - Wu, Guilin; Liu, Hui; Hua, Lei; Luo, Qi; Lin, Yixue; He, Pengcheng; Feng, Shiwei; Liu, Juxiu; Ye, Qing (Frontiers in Plant Science, 2018)
Global warming could increase leaf transpiration and soil evaporation, which can potentially cause water deficit to plants. As valves, leaf stomata can control plant water loss and carbon gain, particularly under water stress conditions. To investigate the responses of stomata to elevated temperature in Schima superba and Syzygium rehderianum, two co-occurring subtropical forest dominant tree species, functional traits related to gas exchange, stomatal anatomy, and drought resistance were measured under control and warming environment (ca. 2°C higher). We found that leaf water potential at both predawn and midday significantly decreased for the two species grown under warming conditions compared with those grown in the control environment. Warming resulted in significant decrease of stomatal size in Syzygium rehderianum, but had no obvious effect on that of Schima superba. By contrast, stomatal density of Schima superba significantly decreased under warming condition, while non-significant change was observed for Syzygium rehderianum. In addition, warming significantly reduced photosynthetic rate, stomatal conductance, and stomatal sensitivity to leaf water potential of Schima superba, but had non-significant effects on those of Syzygium rehderianum. Overall, our results demonstrated that, confronting water deficit caused by elevated temperature, the two co-occurring subtropical tree species responded differently through the adjustment of stomatal morphology and photosynthetic function. Consequently, Syzygium rehderianum was able to maintain similar carbon assimilation as under control environment, while Schima superba showed decrease in carbon gain that might bring adverse effect on its dominancy in subtropical forest community under future climate change.